Power walk activity: a tool adapted for the water sector - Khalid, Sidra; Waqar, Kanwal (International Water Management Institute, 2023)
The Power Walk is a group role-playing exercise designed to prompt reflection on power dynamics, privilege, and social inequalities, adapted for the water sector context. The activity simulates a society where individuals have an equal starting point but depending on their social identities end up in different positions. The game is meant to convey gender equality and social inclusion (GESI) concepts in the water sector.